DIAGENETIC ALTERATION OF MAGNETIC SIGNALS BY ANAEROBIC OXIDATION OF METHANE RELATED TO A CHANGE IN SEDIMENTATION RATE - Riedinger N.; Pfeifer K.; Kasten S.; Garming J.F.L.; Vogt C.; Hensen C. (My University, 2005)
Geochemical and rock magnetic investigations of sediments from three sites on the continental margin off Argentina and Uruguay were carried out to study diagenetic alteration of iron minerals driven by anaerobic oxidation of methane (AOM). The western Argentine Basin represents a suitable sedimentary environment to study nonsteady-state processes because it is characterized by highly dynamic depositional conditions. Mineralogic and bulk solid phase data document that the sediment mainly consists of terrigenous material with high contents of iron minerals. As a typical feature of these deposits, distinct minima in magnetic susceptibility (κ) are observed. Pore water data reveal that these minima in susceptibility coincide with the current depth of the sulfate/methane transition (SMT) where HS− is generated by the process of AOM. The released HS− reacts with the abundant iron (oxyhydr)oxides resulting in the precipitation of iron sulfides accompanied by a nearly complete loss of magnetic susceptibility. Modeling of geochemical data suggest that the magnetic record in this area is highly influenced by a drastic change in mean sedimentation rate (SR) which occurred during the Pleistocene/Holocene transition. We assume that the strong decrease in mean SR encountered during this glacial/interglacial transition induced a fixation of the SMT at a specific depth. The stagnation has obviously enhanced diagenetic dissolution of iron (oxyhydr)oxides within a distinct sediment interval. This assumption was further substantiated by numerical modeling in which the mean SR was decreased from 100 cm kyr−1 during glacial times to 5 cm kyr−1 in the Holocene and the methane flux from below was fixed to a constant value. To obtain the observed geochemical and magnetic patterns, the SMT must remain at a fixed position for ∼9000 yrs. This calculated value closely correlates to the timing of the Pleistocene/Holocene transition. The results of the model show additionally that a constant high mean SR would cause a concave-up profile of pore water sulfate under steady state conditions.